Improving Compliance With The Use PPE at PT. Lintech Duta Pratama Through The PPE Distribution and Inspection Program - Hana, Eka; Friska Ayu; Ratna Ayu Ratriwardani; Saddam Bill Adli Faza Kuswandi (Universitas Nahdlatul Ulama Surabaya, 2024)
Increasing compliance in the use of Personal Protective Equipment (PPE) in the work environment is one of the top priorities in maintaining work safety. This study aims to evaluate the effectiveness of the PPE distribution program and inspection implemented at PT Lintech Duta Pratama in increasing compliance with the use of PPE by employees. The research methodology involves analyzing data before and after the implementation of the program, involving 200 employees as respondents. The results of the study show that before the program was implemented, the compliance rate for the use of PPE only reached 65%. After the implementation of a more structured PPE distribution program and regular inspections, the compliance rate increased significantly to 90%. This increase shows a positive correlation between the PPE distribution program and the frequency of inspections with employee awareness and compliance with the use of PPE in the workplace.